(untitled) (International Journal of Environmental Sciences, 2025)
Silver-doped CuFe2O4 nanoparticles were synthesized using a sol-gel method involving citric acid at ambient temperature. The structure and microstructure of the Ag-doped CuFe2O4 nanoparticles were analyzed in relation to calcination temperature. Characterization of the synthesized nanoparticles was carried out using X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), and transmission electron microscopy (TEM), which were used to confirm the formation of crystalline nanosized Ag-doped CuFe2O4 spinel. The XRD analysis revealed a crystalline inverse spinel structure with a particle size of 15.23 nm, characterized by sharp peaks that indicated a homogeneous single-phase ferrite. The antimicrobial properties of the Ag-doped CuFe2O4 nanoparticles were evaluated against three types of fungi, demonstrating significant antifungal activity. Data clearly indicate that CuFe2O4 nanoparticles with silver doping levels of 1 wt%, 2 wt%, and 3 wt% show enhanced antifungal efficacy compared to pure CuFe2O4. Additionally, the antifungal assay results exhibited superior inhibition from the doped samples versus the pure samples. Ag-doped copper ferrite shows considerable antimicrobial potential and may be applicable for medicinal uses.